Penerapan Problem Based Learning untuk Meningkatkan Keterampilan Berpikir Kritis dan Sikap Mandiri pada Pembelajaran Matematika SD - Syadevi, Wamida Ayu Nabila; Suharyanto, Suharyanto (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2024)
The research is motivated by low level of critical thinking skills and independent attitudes of students in mathematics learning. Because teachers do not vary learning models so that learning seems boring. This is also related to students who tend not to listen while learning is taking place. As a result, students, when learning, are not yet fully able to analyze existing questions and this has an impact on students' low critical thinking skills, as well as working on evaluation questions collaboratively so they are easily dependent on other people. Research conducted to improve students' critical thinking skills and independent attitudes in mathematics learning using the Classroom Action Research method. In this research, observation, interviews and tests were used in the data collection process. In this research, two cycles were carried out on 33 class V students at SDN Ngadirejo 3. In the cycle I, average student obtained 62,65% and go up to 79,96% in cycle II. Apart from that, the independent attitude of each student also increased from 21 to 29 students in working on evaluation questions independently. Can be concluded that applying PBL model in mathematics subjects regarding perimeter and area of flat shapes can go up critical thinking skills and independent attitudes.